IL–18 AND IMMUNITY - E. V. Yakushenko; J. A. Lopatnikova; S. V. Sennikov (Медицинская иммунология, 2014)
Abstract. Interleukin–18 is one of the main cytokines, inducing production of IFNg. It is the important factor of anti–infectious and anti–tumor immunity. The review represent molecular–genetic and biochemical characteristics of IL–18. The data about producers, the structure of the receptor and of IL–18 binding protein, as well as signal transduction in the cell are considered. Besides that, the main immune effects of IL–18 are discussed. (Med. Immunol., 2005, vol.7, № 4, pp 355–364)